2017
DOI: 10.1161/circimaging.117.006979
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Echocardiographic Z Scores Adjusted for Body Surface Area to Age, Sex, Race, and Ethnicity

Abstract: Background Published nomograms of pediatric echocardiographic measurements are limited by insufficient sample size to assess the effects of age, sex, race, and ethnicity. Variable methodologies have resulted in a wide range of Z-scores for a single measurement. This multicenter study sought to determine Z-scores for common measurements adjusted for body surface area (BSA) and stratified by age, sex, race, and ethnicity. Methods and Results Data collected from healthy non-obese children ≤18 years old at 19 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(205 citation statements)
references
References 42 publications
(65 reference statements)
3
163
0
1
Order By: Relevance
“…27 It is possible that future studies could utilise a newly derived multicentre database of normal echocardiograms that measured left ventricular mass similar to the current study to answer these questions. 28…”
Section: Relationship Between Body Size Scaling Variables and Left Vementioning
confidence: 99%
“…27 It is possible that future studies could utilise a newly derived multicentre database of normal echocardiograms that measured left ventricular mass similar to the current study to answer these questions. 28…”
Section: Relationship Between Body Size Scaling Variables and Left Vementioning
confidence: 99%
“…Each method has cited literature supporting its application [29,30], thus it is important for the imager to understand which study to use for accurate z score generation based on their contouring method [28]. Generally speaking, our model differs from the Lopez et al Pediatric Heart Network echo paper [11], in that we found a linear relationship between BSA and cardiac chamber size, whereas they developed a model based upon a ratio estimator indexed to BSA raised to a fitted power. In addition, we found a constant sex difference, indicating modestly larger chamber sizes in males across all age groups.…”
Section: Discussionmentioning
confidence: 91%
“…Others have published smaller series of niche measurements of pediatric cardiac structures, including Doppler assessments of valves, left ventricular (LV) mass [7] and coronary artery dimension [8,9], as well as z scores for cardiac structures in the developing fetus [10]. Most recently, and most comprehensively, Lopez et al published the most robust set of 2D echocardiography measurements that describe normal growth in children over a wide range of BSA, ages and ethnicities [11]. Z scores gauging the relative size of a cardiac structure in children are valuable to the cardiac imaging community, as well as the larger pediatric cardiology and cardiothoracic surgery community to provide standards for decision-making regarding interventions and for the evaluation of outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The design and main results of the Pediatric Heart Network Normal Echocardiogram Database Study were previously published. 1 Briefly, the database was a retrospective collection of demographic and echocardiographic data obtained from healthy North American children ⩽18 years old from 19 congenital cardiac centres (10 Pediatric Heart Network core centres and 9 auxiliary centres) between April, 2013 and October, 2015. The targeted enrolment for the study included 3600 participants, divided into 36 groups, stratified by age (6 groups), race (White, African-American, Other), and gender, with ⩾80% of echocardiograms submitted expected to have all the necessary images to allow for a minimum of 80 echocardiograms per group to be analysed based on power calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The goal was to develop a robust z-score database that accounted for age, race, and gender. 1 The study aimed to overcome limitations of previous echocardiographic z-score databases, including small sample size from single institutions, non-standardised methods for performing and normalising measurements, and limited assessment of the potential effects of race and gender. Despite the detailed study design and considerable time spent planning the study, we encountered unexpected challenges in its implementation.…”
Section: Introductionmentioning
confidence: 99%